2015
DOI: 10.1016/j.geoforum.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, carbon dependency and narratives of transition and stasis in four English rural communities

Abstract: This paper explores the carbon dependency of life in four villages in England, the degree to which residents in these villages are aware of and concerned about this dependency and its relationship to climate change, and the extent to which they undertake actions that might mitigate or adapt to this dependency. The paper identifies high degrees of carbon dependency and awareness and concern about climate change and carbon dependency, although relatively low levels of mitigative or adaptive actions. The paper ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Critical scholars of climate change and community, regularly engage with the multiple meanings of community, and the question ‘what does community do.’ Or, as in Phillips and Dickie's account of community stasis and inaction, what community doesn't do . Wright for instance, who is critical of community's persistently positive associations, also points to the variegated experiences of and pursuit of community within the everyday lives of suburban dwellers, which often include a positive vision.…”
Section: The Multiple Meanings Of Community and Their Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical scholars of climate change and community, regularly engage with the multiple meanings of community, and the question ‘what does community do.’ Or, as in Phillips and Dickie's account of community stasis and inaction, what community doesn't do . Wright for instance, who is critical of community's persistently positive associations, also points to the variegated experiences of and pursuit of community within the everyday lives of suburban dwellers, which often include a positive vision.…”
Section: The Multiple Meanings Of Community and Their Functionsmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51] Or, as in Phillips and Dickie's account of community stasis and inaction, what community doesn't do. 52 Wright 36 for instance, who is critical of community's persistently positive associations, also points to the variegated experiences of and pursuit of community within the everyday lives of suburban dwellers, which often include a positive vision. Van Veelen and Haggett 53 show how multiple forms of place attachment form the basis of disagreements in the context of rural renewable energy projects.…”
Section: Critical Community and Participation In The Global Southmentioning
confidence: 99%
“…These concerns are not unique to rural residents-there is a well-established disjuncture between the recognition of climate change and willingness to take extensive personal action [45]. In work exploring this disjuncture in four rural communities in England, Phillips and Dickie [46] found that residents used various "narratives" to (self-)justify a reluctance to adopt "carbon-and energy-reducing activities such as using public transport more, reducing their car journeys, purchasing a car with a smaller engine, or moving to or building an eco-house" (p. 101). One such narrative was centred around the trade-off between personal costs and public benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The psychological green climate is built on the process of social cognition (Dumont et al, 2017). The psychological environment strongly correlates with work fulfillment, burnout, position actions, and extra-role job success (Phillips and Dickie, 2015). Recent research has discovered a correlation between institutional environment policies, green environment activity, and successful green actions among employees (Norton et al, 2017).…”
Section: Psychological Green Climate As a Mediatormentioning
confidence: 99%